Microglial mechanisms of viable retinal ganglion cell elimination - López, Navita N.; Rodríguez, Yésica Landaverde; Vetter, Monica L. (Frontiers in Cellular Neuroscience, 2025)
Microglia can selectively phagocytose live neurons during normal development and also in response to stress, injury or disease by recognizing phagocytic cues to target cells for elimination. In the developing retina at embryonic stages we previously found that microglia refine retinal ganglion cell (RGC) numbers by targeting non-apoptotic newborn RGCs for phagocytosis, utilizing complement receptor 3 (CR3) to recognize and eliminate RGCs. Here, we investigate additional phagocytic mechanisms and cues that microglia utilize to clear a subset of viable RGCs. Our findings indicate that both Mer tyrosine kinase (Mertk) and CR3 are required for clearance of a subpopulation of embryonic RGCs. In Mertk/CR3 double knockouts, we show that C1q-tagged RGCs accumulate and excess RGCs persist indicating failure of normal clearance by microglia. We also show that microglia target RGCs that have phosphorylated c-JUN (p-cJUN) expression, suggesting stress pathway activation. RGCs with p-cJUN expression also accumulate in Mertk/CR3 double knockout retinas, but this appears to resolve by P0, suggesting this is a transient stress state exhibited by a subset of RGCs that remain viable. By depleting microglia we establish that microglia are not required for p-cJUN induction in RGCs but show that they are the sole source of complement protein C1q, which marks these cells for elimination. Altogether the data suggests that a subset of stressed RGCs are recognized by local microglia that tag them with opsonins for removal using specific recognition receptors.